Optimasi Strategi PT PLN: Analisis Studi Kasus Dengan Pendekatan Five Force Analysis - Zahra Fierza Arzety; Endang Pudji Widjajati (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Electricity is currently a vital resource highly needed by modern society, as the majority of human life activities are related to electricity. This sector is crucial in the execution of development initiatives to seek the enhancement of the well-being and prosperity of the people, enlighten the nation, and boost the people's economy in achieving national development goals. It can be said that electricity has become the primary source of energy in every activity, both in households and industries. PT PLN (Persero) is a state-owned enterprise (BUMN) that has been managing all aspects of electricity in Indonesia for 44 years, aiming to improve the quality of people's lives and focus on customer satisfaction. In order to continue to grow and improve, PT PLN East Java requires analysis and evaluation of the company's current condition to compete externally. Therefore, a method is needed to determine the position and condition of PT PLN East Java using the method from the strategic management course, namely the Five Force Analysis Method.